Ultrasonic features of papillary thyroid microcarcinoma and non-microcarcinoma - ZHANG, XIAO-LI (D.A. Spandidos, 2014)
The present study analyzed the ultrasonic features of papillary thyroid microcarcinoma (PTMC) and papillary thyroid non-microcarcinoma (non-PTMC) with the aim of improving the diagnostic value of ultrasonography. The ultrasonic features of 328 patients with papillary thyroid carcinoma (PTC), as confirmed by pathology, were retrospectively analyzed. Patients were diagnosed with PTMC if the tumor size was ≤10 mm in diameter or non-PTMC if the tumor size was >10 mm in diameter. The shape, ratio of length/width, boundary, echo, peripheral halo ring, calcification, cystic changes, blood flow, lymph node metastasis and additional accompanying thyroid diseases were compared between the patients with PTMC and non-PTMC. In total, 389 nodules were identified in the 328 patients, including 209 PTMC nodules and 180 non-PTMC nodules. The multifocality rate was 15.9% (52/328). Ultrasound scans detected a total of 371 nodules, while 18 PMTC nodules were missed diagnosed and 57 nodules were misdiagnosed as benign nodules. Statistically significant differences in the boundary, ratio of length/width, cystic changes, blood flow and lymph node metastasis were observed between the PTMC and non-PTMC groups (P<0.05). However, no statistically significant differences were observed with regard to the shape, calcification, peripheral halo rings and additional accompanying thyroid diseases between the two groups (P>0.05). Therefore, ultrasound plays an important role in the diagnosis of PTC, with PTMC and non-PTMC exhibiting different ultrasonic performances.